Scalable synthesis of graphitized carbon powder from Prosopis juliflora and its supercapacitve performance. (February 2022) - Sivagaami Sundari, G.; Thileep Kumar, K.; Senthil Kumar, E.; Shanmugaraj, A.M.; Kalaivani, R.; Raghu, S.
Abstract: Herein, we report a scalable synthesis of 3D porous graphitized carbon power (GC) using the one-step carbonization and activation of Prosopis juliflora for symmetric supercapacitor applications. Electron-microscopy (SEM and TEM) showed the optimized GC forms a 3D-foam cluster morphology with a maximum surface area of ∼1183 m 2 g –1, which induces rapid charge transfer reactions. The GC exhibit a prominent Raman 2D peak at ∼2670 cm −1 . The electrochemical performance of the GC has been compared with commercially available carbon for the first-time. The GC showed an exceptional half-cell specific capacitance of ∼415 Fg –1 at 1 Ag –1 and the commercial carbon sample delivered ∼270 Fg –1 at 1 Ag –1, which is very high compared to other reported porous carbon materials obtained from biomass. The GC delivered ∼50% higher power and >90% capacitance retention when compared to the commercial carbon sample with an energy density of ∼47 Whkg −1 and power density of ∼49 kWkg −1 . Thus, the GC electrode material is a green, sustainable, and alternative electrode for use in high energy supercapacitor applications. Graphical abstract: Image 1 Highlights: Carbon powder has been synthesized from Prosopis juliflora for the first time. A specific capacitance of 415 Fg –1 at a scan rate of 10 mVs −1 has been achieved. The material exhibits the 2D peak at 2670 cm-1 in Raman spectroscopy demonstrating its graphitization. The material showed excellent cycling retention of 99% over 10, 000 cycles. The material showed energy density of 47.60 Whkg −1 with a power density of 104.03 kWkg −1. .